Evaluation of Land Suitability for The Development of Fruit Horticultural Crops on Dryland in Banjar Sub- District, Buleleng District (Agrotrop : Journal on Agriculture Science, 2026)
Dryland areas in Banjar Sub-District, Buleleng Regency, possess considerable potential for the development of fruit horticultural crops; however, their utilization has not been optimized due to limited information regarding land suitability and appropriate land management practices. This study aimed to evaluate the actual and potential land suitability for fruit horticultural crops, identify the major limiting factors, and formulate land use recommendations to support sustainable agricultural development. The research was conducted from April to August 2025 through field surveys, soil sampling, laboratory analyses, and land evaluation using a matching method between land characteristics and crop growth requirements. The results indicated that the actual land suitability classes ranged from N (not suitable) to S2 (moderately suitable). The major limiting factors included climatic conditions, particularly temperature and rainfall, soil physical properties such as texture and effective soil depth, and low nutrient availability, especially nitrogen (N), phosphorus (P), and potassium (K). Improvement measures through fertilization, application of organic amendments, and drainage management increased the potential land suitability to S2 (moderately suitable) and S1 (highly suitable) classes in several land units. Quantitatively, these improvement measures reduced soil fertility and soil property constraints, thereby increasing the level of land suitability for horticultural crop cultivation on dryland areas. These findings demonstrate that appropriate soil and water management can substantially improve dryland productivity and support sustainable horticultural development and land-use planning in Banjar Sub-District.
Keywords: land use recommendations; land suitability evaluation; limiting factors; horticultural crops